Tendencias del impuesto a la renta corporativo en Latinoamérica - Villagra Cayamana, Renée Antonieta (2014)
The main objective of this study is to expose the corporative income taxation granted by the legislations of different Latin American countries, trying to identify and analyze trends that emerge from such treatment. This paper does not intend to make a critical or comprehensive analysis of the corporative income taxation. This paper identifies the most important issues of the resident’s income taxation, deductible expenses, non-resident taxation and withholdings, and the anti-avoidance measures introduced by the domestic legislation of Latin American countries in order to avoid the base erosion.